A specific loop in human DNA polymerase mu allows switching between creative and DNA-instructed synthesis - Juárez, Raquel (Oxford University Press, 2006)
Human DNA polymerase mu (Polμ) is a family X member that has terminal transferase activity but, in spite of a non-orthodox selection of the template information, displays its maximal catalytic efficiency in DNA-templated reactions. As terminal deoxynucleotidyl transferase (TdT), Polμ has a specific loop (loop1) that could provide this enzyme with its terminal transferase activity. When loop1 was deleted, human Polμ lacked TdT activity but improved DNA-binding and DNA template-dependent polymerization. Interestingly, when loop1 from TdT was inserted in Polμ (substituting its cognate loop1), the resulting chimaera displayed TdT activity, preferentially inserting dGTP residues, but had a strongly reduced template-dependent polymerization activity. Therefore, a specialized loop in Polμ, that could adopt alternative conformations, appears to provide this enzyme with a dual capacity: (i) template independency to create new DNA information, in which loop1 would have an active role by acting as a ‘pseudotemplate’; (ii) template-dependent polymerization, in which loop1 must allow binding of the template strand. Recent in vivo and in vitro data suggest that such a dual capacity could be advantageous to resolve microhomology-mediated end-joining reactions.